The combination of decitabine with multi-omics confirms the regulatory pattern of the correlation between DNA methylation of the CACNA1C gene and atrial fibrillation - Yang, Yuling; Li, Qijun; Liu, Xiaoning; Shao, Caixia; Yang, Heng; Niu, Siquan; Peng, Hong; Meng, Xiangguang (Frontiers in Pharmacology, 2024)
BackgroundStudies have shown that DNA methylation of the CACNA1C gene is involved in the pathogenesis of various diseases and the mechanism of drug action. However, its relationship with atrial fibrillation (AF) remains largely unexplored.ObjectiveTo investigate the association between DNA methylation of the CACNA1C gene and AF by combining decitabine (5-Aza-2′-deoxycytidine, AZA) treatment with multi-omics analysis.MethodsHepG2 cells were treated with AZA to observe the expression of the CACNA1C gene, which was further validated using gene expression microarrays. Pyrosequencing was employed to validate differentially methylated sites of the CACNA1C gene observed in DNA methylation microarrays. A custom DNA methylation dataset based on the MSigDB database was combined with ChIP-sequencing and RNA-sequencing data to explore the regulatory patterns of DNA methylation of the CACNA1C gene.ResultsTreatment of HepG2 cells with three different concentrations of AZA (2.5 µM, 5.0 µM, and 10.0 µM) resulted in 1.6, 2.5, and 2.9-fold increases in the mRNA expression of the CACNA1C gene, respectively, compared to the DMSO group, with statistical significance at the highest concentration group (p < 0.05). Similarly, AZA treatment of T47D cells showed upregulated mRNA expression of the CACNA1C gene in the gene expression microarray results (adj P < 0.05). DNA methylation microarray analysis revealed that methylation of a CpG site in intron 30 of the CACNA1C gene may be associated with AF (adj P < 0.05). Pyrosequencing of this site and its adjacent two CpG sites demonstrated significant differences in DNA methylation levels between AF and sinus rhythm groups (p < 0.05). Subsequent multivariate logistic regression models confirmed that the DNA methylation degree of these three sites and their average was associated with AF (p < 0.05). Additionally, the UCSC browser combined with ChIP-sequencing revealed that the aforementioned region was enriched in enhancer markers H3K27ac and H3K4me1. Differential expression and pathway analysis of RNA-sequencing data ultimately identified ATF7IP and KAT2B genes as potential regulators of the CACNA1C gene.ConclusionThe DNA methylation levels at three CpG sites in intron 30 of the CACNA1C gene are associated with AF status, and potentially regulated by ATF7IP and KAT2B.